A Normative Study on English Translation of Metro Public Signs in China under the Cognitive Translatology: A Case Study of Chengdu the Host City for the Universiade - Liu, Haiou; Teng, Luyan; Kong, Lingcui (Quality in Sport, 2023)
With the acceleration of its internationalization, China is faced with epochal task of optimizing its international-standard linguistic environment, which is especially impending for Chengdu, the host city for the Universiade. The neo-analysis, at first, sorts out and analyzes different versions of official translation norms for toponyms through document research, as well as from the first-hand resources on public signs of rail transit from TFL and MTA, and then, continues the empirical case study under the theoretical guidance of Cognitive Translatology. This paper has proposed several translation principles and a new method - Conceptual Motivation Mapping - for public signs, attempting to explore the way to build up its international discourse system consistent with the status of Chengdu as a global hub.